Mechanical property enhancement in concrete composites with hybrid polypropylene fibre reinforcement - Chiang Ti Tan; Ming Kun Yew; Ming Chain Yew; Foo Wei Lee; Siong Kang Lim; Jing Han Beh; Jin Chai Lee; Jee Hock Lim (Scientific Reports)
Abstract Hybrid fibre-reinforced concrete is a specialised construction material known for its enhanced mechanical strength and durability. However, there is limited research available on hybridising three types of fibre in concrete. In this study, concrete was enhanced by incorporating three types of polypropylene (PP) fibre, namely Macro, Barchip and Monofilament PP fibre, with volume fractions of 0%, 0.1%, 0.2%, and 0.3%. Recycled granite powder was also used to partially replace fine aggregate to improve matrix density and promote sustainability. Results revealed that increasing fibre volume fractions significantly boosted mechanical properties. The Macro-Barchip-Monofilament (MBM) PP fibre mixture showed superior strength performance compared to the Barchip-Monofilament (BM) PP fibre mixture, with the MBM mix with fibre volume fractions of 0.3% achieving compressive, splitting tensile, and flexural strength improvements of 4.84%, 10.02%, and 15.83%, respectively. These enhancements were largely due to the combined effects of the hybrid PP fibres. While Barchip PP fibre effectively mitigated crack propagation, Macro PP fibre offered fine reinforcement to limit crack widths. Meanwhile, the dispersion of Monofilament PP fibre within the concrete matrix contributed to increased homogeneity. Nevertheless, the addition of hybrid PP fibres adversely affected workability, as evidenced by a 58.33% drop in slump values and an 84.62% rise in Vebe time. Furthermore, the ultrasonic pulse velocity (UPV) test highlighted advancements in concrete quality and scanning electron microscope (SEM) analysis demonstrated that fibre reinforcement enhanced the microstructure and bonding within the concrete. Post-cracking performance assessments confirmed the role of hybrid PP fibres in improving residual strength. Altogether, the findings indicate that hybrid PP fibre-reinforced concrete holds significant potential for creating durable and sustainable building materials.